Estimation of the catchability coefficient of purse seine using split beam echo sounders - Zakaria, M Z; Samo, K B; Hermawan, M; Ambak, M A (Indian Journal of Fisheries, 2011)
This paper aims to estimate the catchability coefficient of purse seine net bycomparing the fish abundance estimated through acoustic technique by using splitbeam echo sounders and the true catch. The fish were caught in the coastal watersaround Pulau Kapas, Kuala Terengganu within 0512.04' to 05°19.38'N latitude and103°13.95' to 103°19.53'E longitude using a purse seine boat with 15 m lengthoperating a net with head rope of 256 m in length, 88 m depth and with meshsize of 24.5 mm. Based on six successful experimentations, the catchabilitycoefficient obtained ranges from 0.84 to 0.98. Ox-eye scad (Selar boops) was themost abundant species caught followed by Indian mackeral (Rastrelligerkanagurta).